Avaliação toxicogenética, antioxidante e fitoquímica dos extratos de Cissus verticillata (L.) Nicolson & C. E. Jarvis (Vitaceae) - Oliveira, Augusto César Santos de (2021)
Cissus verticillata Nicolson & C. E. Jarvis is a plant species widely used by the population in the treatment of diseases. Its use is due to its biological activities, such as its antiglycemic, anticonvulsant, antirheumatic, among others. In view of its importance in folk medicine, it is necessary to evaluate the plant with a toxicogenetic approach, as, even with beneficial characteristics for health, it may have some harmful effect. This work aimed to evaluate the toxicogenetic and antioxidant activities and chemical characterization of aqueous and ethanolic extracts of Cissus verticillata, using Allium cepa (L.) as test organism. For this, the two types of extracts were characterized and used as treatments in the phytotoxicity, cytotoxicity, genotoxicity and mutagenicity assays, at concentrations of 100, 75, 50, 25 and 12.5 (% v/v). The chemical characterization of the extracts revealed the presence of classes of metabolites such as flavonoids, sugars and tannins. A reduction in A. cepa seed germination was observed at concentrations 100, 75, 50, 25 (% v/v) of the ethanol extract and root growth at all concentrations, except at concentrations 25 and 12.5 (% v /v) of the aqueous extract. The cell cycle of the meristematic cells of A. cepa roots was also affected by the reduction of the Mitotic Index, at the concentrations 75, 50, 25 (% v/v) of the ethanol extract and at the concentration of 100 (% v/v) of the aqueous extract. In the analysis of genotoxic and mutagenic activity, no significant alteration was found. Using the DPPH method, it was possible to identify the antioxidant capacity of the extracts, where the ethanol extract showed a better activity when compared to the aqueous extract, having an EC50 of 364.65 µg.mL-1 and 982.51 µg.mL-1 respectively. The data obtained in this study indicate that the extracts of C. verticillata, even causing changes in the mitotic index did not cause changes in the DNA molecule of the meristematic cells of Allium cepa, this fact may be related to the presence of the antioxidant activity of the extracts due to the presence of of phenolic groups such as flavonoids and tannins. These data contribute to a safer use of the plant by the population at the concentrations tested.